2015
DOI: 10.1016/j.radphyschem.2015.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen radiolytic release from zeolite 4A/water systems under γ irradiations

Abstract: International audienceWe irradiated samples of zeolites 4A which contained different quantities of water. We measured the quantity of hydrogen released. Hydrogen radiolytic yields, present two maxima, for two water loading ratios. Hydrogen release is enhanced by the strength of the zeolite/water interaction. Hydrogen release is enhanced by the quantity of water interacting with the zeolite. a b s t r a c t Although the radiolysis of bulk water is well known, some questions remain in the case of adsorbed or con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 25 publications
(37 reference statements)
1
13
1
Order By: Relevance
“…It is worth noting that in irradiated zeolites [66] the H2 radiolytic yield is lower than 10 -8 mol J -1 at the lowest water content whereas here, the yield we determine in dry S3 is significantly higher than this value. At this low water content, water is immobilized in the cages of zeolites while it is confined, but mobile in the 2D interlayer space of cement paste.…”
Section: Radiation-induced H2 Productioncontrasting
confidence: 64%
“…It is worth noting that in irradiated zeolites [66] the H2 radiolytic yield is lower than 10 -8 mol J -1 at the lowest water content whereas here, the yield we determine in dry S3 is significantly higher than this value. At this low water content, water is immobilized in the cages of zeolites while it is confined, but mobile in the 2D interlayer space of cement paste.…”
Section: Radiation-induced H2 Productioncontrasting
confidence: 64%
“…The slope of the associated linear regression is the hydrogen apparent radiolytic yield (in mol/J). For zeolite A the obtained values of 2.1 × 10 −8 and 1.8 × 10 −8 mol/J respectively for zeolites beads and powder are very close to the yield measured in the literature by L. Frances 30 and by Nakashima 43 for zeolite 4A saturated with water.…”
Section: Individual Componentssupporting
confidence: 88%
“…The hydrogen production by water radiolysis in zeolite was also studied, 30,31 and zeolites type A4 (Na) were subject to numerous investigations as they were used to store tritiated water, or for the decontamination of Three Mile Island water. With zeolites, the importance of energy transfer from the matrix to the porous water was clearly observed.…”
mentioning
confidence: 99%
“…Previous studies dealing with the radiolysis of zeolites with adsorbed water agree to the point that irradiation of the solid matrices of the zeolites induces decomposition of water in the pores resulting in H 2 production. The energy/charge transfer from the zeolites was confirmed by pulse radiolysis studies of excess electrons in hydrated zeolites. The pulse radiolysis studies concluded that generation of excess electrons hydrated in the zeolite pores occurred at yields greater than hydrated electron (e – aq ) during the radiolysis of bulk water. The high yields of e – aq would qualitatively explain the H 2 production by the irradiation of hydrated zeolites because e – aq is a main precursor of H 2 in water radiolysis. , However, understanding radiation-induced reactions in zeolites is not sufficient to estimate the yield of H 2 because the reaction scheme of H 2 production is not well-defined .…”
Section: Introductionmentioning
confidence: 74%